Tax loss carryforward disclosure and uncertainty - Vanessa Flagmeier; Jens Müller (Arbeitskreis Quantitative Steuerlehre (arqus), 2016)
We examine whether companies voluntarily disclose additional information about tax loss carryforwards when the recoverability is more uncertain. With this study, we aim to explain part of the huge cross-sectional variation in the tax footnote. To assess disclosure behavior, we hand collect data from notes of large German firms' IFRS financial statements and identify voluntarily disclosed information beyond the requirements of IAS 12. We find that uncertainty about the usability of tax losses has a significantly negative relation to the amount and quality of disclosure, controlling for other disclosure determinants derived from prior literature. These findings are robust for several indicators representing information and income uncertainty. Our findings suggest that managers anticipate the investors' need for more private information and disclose them voluntarily to send a signal of credibility to the market participants. It can be assumed that disclosing this information is less costly than facing potential risk premiums demanded by investors leading to higher cost of capital. This result indicates that part of the cross-sectional variation in the tax footnote can be explained by differing expectations to use the tax losses.
Keywords: 330; tax loss carryforwards; disclosure; uncertainty; capital cost; deferred taxes